Paléohydrographie et archéologie de l'espace en pays tricastin : de l'archéologie aérienne à la télédetection satellitaire - Ibtissem Tounsi (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
The Tricastin region (France - Drôme and Vaucluse Departments) is one of the regions for which the most information on the ancient agrarian structure is available. It is the only region of the Roman Empire for which there exists a rural cadastral plan drawn up during antiquity (the B Cadastre of Orange), and of which fragments have been found engraved on marble slabs. This incomplete but extremely precise cartography represents a regular breakdown of the land into square units (centuries), still partially perceptible in the landscape, transferred onto a summary geographical backdrop on which the water courses are distinguished from the major roads. This exceptional and unique information has been supplemented by an archaeological map drawn up from field and air surveys, and from recent observations made during the archaeological survey carried out along the layout of the future Mediterranean TGV railway line. Given this situation, it is interesting to determine the specific contribution that satellite remote sensing can make towards the information obtained from the geo-archaeological investigation and the archaeomorphology based on cartography and photointerpretation. The result of the interpretation of certain processing operations shows the advantage and the capacity of remote sensing to supplement information obtained from photointerpretation and archaeological digs.